2003
DOI: 10.1177/106591290305600401
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Wars Fought by Established Democracies: Do Institutional Constraints Matter?

Abstract: Extant re s e a rch has shown that cross-national variations in the level of a country ' s democracy tend to be re l a t e d to its propensity to be involved in external conflict. The dyadic version of the theory of democratic peace contends that democracies rare l y, if ever, fight each other, and it is strongly supported by the available evidence. The monadic version, suggesting that democracies are in general more peaceful re g a rdless of the nature of the other p a rty involved in a relationship, has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 60 publications
0
49
0
1
Order By: Relevance
“…This contrasts with Auerswald (1999), who finds coalition governments restrained in their use of force. Regarding the parliamentary-presidential distinction Reiter and Tillman (2002), as well as Leblang and Chan (2003), report no significant results. Concerning electoral rules, however, these studies find that proportional representation systems are less likely to get involved in war (ibid.)…”
Section: Democracy and War Involvementmentioning
confidence: 68%
“…This contrasts with Auerswald (1999), who finds coalition governments restrained in their use of force. Regarding the parliamentary-presidential distinction Reiter and Tillman (2002), as well as Leblang and Chan (2003), report no significant results. Concerning electoral rules, however, these studies find that proportional representation systems are less likely to get involved in war (ibid.)…”
Section: Democracy and War Involvementmentioning
confidence: 68%
“…Prins and Sprecher (1999) somewhat surprisingly found that coalition governments are more likely to reciprocate military force during crises than are single-party governments. Leblang and Chan (2001) found that proportional representation systems are less likely to fight wars.…”
Section: Domestic Political Institutions and International Conflict Bmentioning
confidence: 97%
“…Leblang and Chan (2003) dismiss the importance of intra-legislative and executive-legislative constraints and argue that electoral systems are the most important institutional restraint on governments' war involvement. Similarly, Clark and Nordstrom (2005: 253) conclude that 'systemic differences between democracies (i.e., presidential, parliamentary) exert little systematic effect on conflict propensity'.…”
Section: The Monadic Perspective and 'Unpacking Democracies'mentioning
confidence: 98%